„RARYTNE” CZASY. O PRZEŁOMIE ROMANTYCZNYM W KSIĘGARZU ULICZNYM WŁADYSŁAWA SYROKOMLI - Zawadzka, Danuta (Colloquia Litteraria, 2017)
The article is interested in looking at the dynamics of the Romantic turning point from the perspective of the changes in the book market in Vilnius in the first half of the nineteenth century. These changes are the subject of literary and historiographical texts by Adam Mickiewicz, Joachim Lelewel, and Władysław Syrokomla. The author focuses primarily on Syrokomla’s Księgarz uliczny [Street bookseller], analysing it in the context of the works of the Romanticism ‘lawgivers’ as an indirect testimony to the evolution of literary preferences and external shape of books, their circulation, types of readers, and bookselling trends.